2006
DOI: 10.1523/jneurosci.2783-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated Region- and Cell-Specific Downregulation of Individual KChIP Auxiliary Subunit Isotypes in Kv4.2 Knock-Out Mouse Brain

Abstract: Kv4 family voltage-gated potassium channel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
78
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 18 publications
12
78
1
Order By: Relevance
“…Expression levels of 15 other proteins in the hippocampus also were analyzed with Western blotting, including other K ϩ channel proteins potentially underlying neuronal A-type K ϩ currents: Kv4.3, Kv1.4, and Kv3.4; the H channel proteins HCN1 and HCN2; the AMPA-type glutamate receptor proteins GluR1 and GluR2/3; two membrane-anchoring proteins enriched in the postsynaptic area, SAP97 and PSD-95; and proteins that functionally or physically associate with Kv4.2 such as NCS1, DPPX, a secretory-type protein containing a pentraxin domain (PTX3), and KChIP1, KChIP2, and KChIP3 (Rhodes et al, 2004;Menegola and Trimmer, 2006 (Fig. 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Expression levels of 15 other proteins in the hippocampus also were analyzed with Western blotting, including other K ϩ channel proteins potentially underlying neuronal A-type K ϩ currents: Kv4.3, Kv1.4, and Kv3.4; the H channel proteins HCN1 and HCN2; the AMPA-type glutamate receptor proteins GluR1 and GluR2/3; two membrane-anchoring proteins enriched in the postsynaptic area, SAP97 and PSD-95; and proteins that functionally or physically associate with Kv4.2 such as NCS1, DPPX, a secretory-type protein containing a pentraxin domain (PTX3), and KChIP1, KChIP2, and KChIP3 (Rhodes et al, 2004;Menegola and Trimmer, 2006 (Fig. 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that Kv4.2 KO mice have decreased KChIP1-3 auxiliary subunit protein levels Menegola and Trimmer 2006), which are critical regulators of Kv4.2 activity and expression (Birnbaum et al 2004). While the role of KChIP1 and KChIP2 in behavior has not been evaluated, KChIP 3 KO mice have recently been reported to have enhanced memory in contextual fear conditioning (Alexander et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…com/Electrophysiology/IChMASCOT/) and IonChannelLab (67) based on a previously published gating model for Kv4.3 expressed with KChIP1 (40). This model was modified by eliminating inactivated states I 5 and I 6 arising from the open state. Data from wild-type channels were fitted using IChMASCOT, setting the initial values of kinetic parameters to those of Beck et al (40).…”
Section: Methodsmentioning
confidence: 99%
“…KCND2 encodes the Kv4.2 voltage-gated K + channel. Kv4.2 and other members of the Kv4 family serve as the pore-forming subunits in inactivating, somatodendritic A-type K + (I SA ) channels, which are widely expressed in the brain (2)(3)(4)(5)(6)(7)(8). Kv4.2 is the sole pore-forming subunit in I SA channels found in pyramidal cells in the CA1 region of the hippocampus (6,7).…”
mentioning
confidence: 99%